Aerobic Exercise Decrease Cholesterol Levels in Type 2 Diabetes Mellitus Patients - Triwibowo, Cecep; Nurjannah, Evi; Fitriyana, Ikha; Fauziyah, Yulia (Jurnal Keperawatan Soedirman, 2018)
Elevated cholesterol level is one of the risks for cardiovascular disease in diabetes mellitus. Exercise is one of therapy in patients with diabetes mellitus. The purpose of this study is to determine the effect of exercise on decrease cholesterol levels in patients with diabetes mellitus. This study used pre-post test one group design. Twenty-two patients with diabetes mellitus followed the intervention which is a twice a week exercise for 4 weeks. Cholesterol levels were measured before and after exercise. Data were analyzed by dependent T-test. Cholesterol levels in patients with diabetes mellitus before the exercise reached 261.18±49.013 mg/dL and after intervention decreased to 224.41±26 mg/dL. Dependent t-test showed differences in cholesterol levels before and after exercise in patients with diabetes mellitus (p<0.05). Exercise can lower cholesterol levels in patients with diabetes mellitus.